2006
DOI: 10.1111/j.1474-8673.2006.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic receptor function, density and G‐protein coupling in the overactive diabetic rat bladder

Abstract: 1 Bladder smooth muscle sensitivity to muscarinic agonists is increased in the overactive bladder. Treatment of rats with streptozotocin induces a diabetic state in which the bladder muscle is overactive and also supersensitive to muscarinic agonists. This study has examined bladder contraction, muscarinic receptor density and receptor/G-protein coupling in the streptozotocin-induced overactive bladder of the rat. 2 Diabetes was induced by a single intraperitoneal dose of streptozotocin. Seven days later contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 26 publications
4
33
0
2
Order By: Relevance
“…Mechanisms governing the enhancement of contractions have been suggested in the SHR. An increase in the total number of muscarinic receptors and/or the level of sensitization of the receptor induced the dysfunction (Sherer et al, 2000;Stevens et al, 2006). In addition, bladder dysfunction in the absence of alterations of muscarinic receptor was also documented (Schneider et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms governing the enhancement of contractions have been suggested in the SHR. An increase in the total number of muscarinic receptors and/or the level of sensitization of the receptor induced the dysfunction (Sherer et al, 2000;Stevens et al, 2006). In addition, bladder dysfunction in the absence of alterations of muscarinic receptor was also documented (Schneider et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Kamata et al (1992) have also shown that the enhanced contractile response to ACh in detrusor strips of urinary bladders from STZ-induced diabetic rats were associated with an increased population of muscarinic receptors. Furthermore, the overactivity was characterized by an enhanced sensitivity to carbachol, partly due to an increase in receptor density, but without change in receptor/G-protein coupling (Hampel et al, 2003;Mumtaz et al, 2006;Stevens et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Denervation and decentralization induce super-sensitivity to cholinergic stimuli, as been observed in the rat bladder [109] , which also occurs after capsaicin treatment [110] . In the denervated rat bladder Color version available online and in the bladder of spinal cord-injured rats, the expression of muscarinic M 2 receptors increases [111][112][113] , while, in diabetic rats, a super-sensitivity to cholinergic stimuli occurs concomitantly with increments in muscarinic receptor density and in muscarinic M 3 receptor expression [114][115][116] . Modulations in the cholinergic bladder contraction also occur during cystitis [78,108] .…”
Section: Pathophysiological and Trophic Effectsmentioning
confidence: 99%